Seeding Rate and Nitrogen Application Effects on Spring Oat and Triticale Forage - A. Obour; J. D. Holman; A. Schlegel (Kansas Agricultural Experiment Station Research Reports, 2018)
Spring oat and triticale are important forage crops in dryland and limited irrigated crop production systems in western Kansas. Previous research in western Kansas showed that growing spring forages in place of fallow reduced soil erosion and increased fallow precipitation use efficiency compared to summer fallow, and increased profitability compared to fallow in years with average to above average rainfall. Despite the great potential of spring forages, information on seeding rate and nitrogen fertilizer recommendations are limited. These management practices can affect forage productivity and nutritive value. Current N fertilizer recommendations for oat and triticale are based on a very limited dataset. In dryland crop production systems in western Kansas, cool-season forages are usually planted in the spring into winter wheat (Triticum aestivumL.) or a summer crop (corn or grain sorghum) stubble. Residual nutrients from the previous crop could provide adequate nutrients for the spring forage crop. However, lower spring temperatures and N immobilization from the previous crop residue often limit early-season N availability for oat or triticale forage. Additional fertilizer application may be needed to boost forage production. Adequate fertility might increase tillering and yield potential, even at lower seeding rates. Moreover, N application in excess of crop uptake can results in environmental quality degradation, economic loss, and forages high in nitrate concentration. It is therefore imperative that site-specific N fertilizer research is conducted to fine tune N fertilizer rates for these cool-season forages to improve yields and environmental quality. Seeding rate is an important crop management practice that affects forage production. It is suggested that spring oat and triticale grown for forage be planted at 25 to 50% greater seeding rates than when managed for grain production. The increase in plant density will allow for greater early crop establishment, smaller stems, and increased DM production. To our knowledge, effects of seeding rate on oat or triticale forage DM production and its interaction with N fertilizer rates has not been extensively studied in semiarid dryland environments. Determining the optimum seeding rate for oat and triticale is important because seed costs constitute a significant component of the variable cost in forage production systems. The objectives of this study were to (1) determine N fertilizer rate effects on DM production and nutritive value for oat and triticale forage, and (2) quantify effect of seeding rate on oat and triticale forage yield and its interaction with N fertilizer application under dryland conditions in western Kansas.
Keywords: Nitrogen fertilization; nitrogen application; seeding rate; spring oat; triticale